Use of complementary and alternative medicine (CAM) in Sweden: a cross-sectional survey - Jenny-Ann Brodin Danell; Kathrin Wode; Miek Jong; Agnete Egilsdatter Kristoffersen; Esther van der Werf; Johanna Hök Nordberg (Scandinavian Journal of Primary Health Care)
Aims The aim of this study was to describe the prevalence, associations, and reasons for the use of complementary and alternative medicine (CAM) in Sweden, as well as to further explore possible self-perceived outcomes including adverse effects as well as the sources of information used.Methods Data were collected by a cross-sectional survey, administered by computer assisted telephone interviews, in June 2020 (n = 500), during the first three months of the COVID-19 pandemic. The survey was a modified version of the International Questionnaire to measure use of Complementary and Alternative Medicine (I-CAM-Q) instrument.Results 63.6% of respondents reported use of CAM. The most common reasons for use were to improve general well-being and/or to treat long-term illness or its symptoms. Very few used CAM to prevent or treat COVID-19. The most used CAMs were natural remedies and dietary supplements (50%), followed by self-help practices (33.2%) and consultation of CAM providers (13%). Women, those of older age (40+), and living in larger cities were more likely to use CAMs compared to the entire sample. Household income or level of education did not predict CAM use. Few adverse effects were reported. The main sources for information were media and the Internet followed by family and friends.Conclusions This study contributes with updated knowledge about Swedish citizens’ use of CAM. The results are important to inform health care policy about patterns of CAM use among Swedish citizens.